PENGARUH PENGALAMAN DAN PROFESIONALISME AKUNTAN FORENSIK TERHADAP KUALITAS BUKTI AUDIT GUNA MENGUNGKAP FRAUD - Dewi Yuniarti R, Rozmita; Tiara, Elsa (Jurnal Riset Akuntansi dan Keuangan, 2015)
The purpose of this study is to find out how the influence of forensic accountant's experience and professionalism on the quality of audit evidence to reveal fraud. Hypothesis in this research is experience of forensic accountant have positive effect to quality of audit evidence to reveal fraud and professionalism of forensic accountant have positive effect to quality of audit evidence to reveal fraud. The research method used is associative method. While the technique of data analysis using correlation coefficient analysis and coefficient of determination analysis. Quantitative data is the primary data. Primary data in the form of questionnaires collected from forensic accountants at the Representative Board of Finance and Development of West Java Province. The results showed that forensic accountant experience and forensic accountant professionalism positively influence the quality of audit evidence to reveal fraud